Zeolite-supported nanoscale zero-valent iron for immobilization of cadmium, lead, and arsenic in farmland soils: Encapsulation mechanisms and indigenous microbial responses. (May 2020) - Li, Zhangtao; Wang, Lu; Wu, Jizi; Xu, Yan; Wang, Fan; Tang, Xianjin; Xu, Jianming; Ok, Yong Sik; Meng, Jun; Liu, Xingmei
Abstract: Zeolite-supported nanoscale zero-valent iron (Z-NZVI) has great potential for metal(loid) removal, but its encapsulation mechanisms and ecological risks in real soil systems are not completely clear. We conducted long-term incubation experiments to gain new insights into the interactions between metal(loid)s (Cd, Pb, As) and Z-NZVI in naturally contaminated farmland soils, as well as the alteration of indigenous bacterial communities during soil remediation. With the pH-adjusting and adsorption capacities, 30 g kg −1 Z-NZVI amendment significantly decreased the available metal(loid) concentrations by 10.2–96.8% and transformed them into strongly-bound fractions in acidic and alkaline soils after 180 d. An innovative magnetic separation of Z-NZVI from soils followed by XRD and XPS characterizations revealed that B-type ternary complexation, heterogeneous coprecipitation, and/or concurrent redox reactions of metal(loid)s, especially the formation of Cd3 (AsO4 )2, PbFe2 (AsO4 )2 (OH)2, and As 0, occurred only under specific soil conditions. Sequencing of 16S rDNA using Illumina MiSeq platform indicated that temporary shifts in iron-resistant/sensitive, pH-sensitive, denitrifying, and metal-resistant bacteria after Z-NZVI addition were ultimately eliminated because soil characteristics drove the re-establishment of indigenous bacterial community. Meanwhile, Z-NZVI recovered the basic activities of bacterial DNA replication and denitrification functions in soils. These results confirm that Z-NZVI is promising for the long-term remediation of metal(loid)s contaminated farmland soil without significant ecotoxicity. Graphical abstract: Image 1 Highlights: Z-NZVI combined the advantages of pH adjustment and adsorption. Z-NZVI decreased available Cd, Pb, and As by 10.21–96.79% in acid and alkaline soils. B-type ternary complexation, heterogeneous coprecipitation, and redox occurred. The dynamic impacts of Z-NZVI on indigenous bacterial communities were discussed. The secondary mineralization of Z-NZVI bonded metal(loid)s and improved soil quality. Abstract : The encapsulation mechanisms and microbial responses of Z-NZVI were investigated.